3|6-y|=18

Divide each term in 3|6-y|=18 by 3.

3|6-y|3=183

Cancel the common factor of 3.

Cancel the common factor.

3|6-y|3=183

Divide |6-y| by 1.

|6-y|=183

|6-y|=183

Divide 18 by 3.

|6-y|=6

|6-y|=6

Remove the absolute value term. This creates a ± on the right side of the equation because |x|=±x.

6-y=±6

Set up the positive portion of the ± solution.

6-y=6

Move all terms not containing y to the right side of the equation.

Subtract 6 from both sides of the equation.

-y=6-6

Subtract 6 from 6.

-y=0

-y=0

Multiply each term in -y=0 by -1

Multiply each term in -y=0 by -1.

(-y)⋅-1=0⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=0⋅-1

Multiply y by 1.

y=0⋅-1

y=0⋅-1

Multiply 0 by -1.

y=0

y=0

y=0

Set up the negative portion of the ± solution.

6-y=-6

Move all terms not containing y to the right side of the equation.

Subtract 6 from both sides of the equation.

-y=-6-6

Subtract 6 from -6.

-y=-12

-y=-12

Multiply each term in -y=-12 by -1

Multiply each term in -y=-12 by -1.

(-y)⋅-1=(-12)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=(-12)⋅-1

Multiply y by 1.

y=(-12)⋅-1

y=(-12)⋅-1

Multiply -12 by -1.

y=12

y=12

y=12

The solution to the equation includes both the positive and negative portions of the solution.

y=0,12

Solve for y 3|6-y|=18